2010
DOI: 10.1093/jxb/erq317
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of photosystem II photochemistry and carbon assimilation and related changes in chlorophyll and protein contents during the rehydration of desiccated Xerophyta scabrida leaves

Abstract: Recovery of photosynthesis in rehydrating desiccated leaves of the poikilochlorophyllous desiccation-tolerant plant Xerophyta scabrida was investigated. Detached leaves were remoistened under 12 h light/dark cycles for 96 h. Water, chlorophyll (Chl), and protein contents, Chl fluorescence, photosynthesis–CO2 concentration response, and the amount and activity of Rubisco were measured at intervals during the rehydration period. Leaf relative water contents reached 87% in 12 h and full turgor in 96 h. Chl synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 57 publications
2
15
0
Order By: Relevance
“…3 and Table 2). Similar results were reported by Augusti et al (2001), Fv/Fm ratio of R. serbica was significantly decreased after RWC was 30-40 % and increased 24 h after rehydration. In addition, Péli et al (2005) showed that Fv/Fm ratio of H. rhodopensis decreased after 7-10 days of dehydration.…”
Section: Imaging Of Chlorophyll Fluorescence and Photosynthetic Activitysupporting
confidence: 90%
See 4 more Smart Citations
“…3 and Table 2). Similar results were reported by Augusti et al (2001), Fv/Fm ratio of R. serbica was significantly decreased after RWC was 30-40 % and increased 24 h after rehydration. In addition, Péli et al (2005) showed that Fv/Fm ratio of H. rhodopensis decreased after 7-10 days of dehydration.…”
Section: Imaging Of Chlorophyll Fluorescence and Photosynthetic Activitysupporting
confidence: 90%
“…In addition, the RWC of R. nathaliae decreased from 94.5 % to 3.6 % during dehydration (Jovanoviç et al 2011). Kinetics of relative water content during dehydration-rehydration cycle was reported from other authors in R. serbica (Augusti et al 2001;Quartacci et al 2002;Veljovic-Jovanoviç et al 2006;Sgherri et al 2004) and Haberlea rhodopensis (Nagy- Deri et al 2011;Mihailova et al 2011;Djilianov et al 2011;Georgieva et al 2010).…”
Section: Relative Water Contentsupporting
confidence: 54%
See 3 more Smart Citations